Morphological changes in the renal corpuscle cortex after two-week administration of nalbuphine and after its withdrawal - Vilkhova , I.V.; Podolyuk , M.V. (Морфологія / Morphologia / Morfologìâ, 2025)
Relevance. Narcotic analgesics (opioids) are widely used in medicine for pain relief in severe injuries, cancer, and the postoperative period. At the same time, their strong effect on the central nervous system and high risk of addiction pose difficult challenges for science and society. The use of opioids, both for medical reasons and in individuals who abuse narcotic drugs, is one of the causes of acute and chronic kidney damage, since most narcotic analgesics or their metabolites are excreted through the kidneys and lead to damage to their structure and function. The aim of our study was to determine changes in the renal corpuscle four weeks after discontinuation of nalbuphine after two weeks of its use. Methods. Histological preparations were prepared according to the generally accepted method. Staining was performed with hematoxylin and eosin. The experimental study was conducted on sexually mature male rats of the “Wistar” line divided into two experimental groups. Results. At the end of the second week of the experiment, with daily administration of nalbuphine, the following changes in the structural organization of the kidneys were observed: overflow with erythrocytes and expansion of the capillary loops of the glomeruli, their hypercellularity, expansion and edema of the mesangial matrix of the renal corpuscles. Four weeks after drug withdrawal, it was found that the renal glomeruli of the subcapsular nephrons were more affected than the renal corpuscles located in the intracortical and juxtamedullary regions of the cortex. The capillary loops of most renal glomeruli of the cortex were dilated and crowded with erythrocytes. The connective tissue of the outer leaf of the Shumlyansky-Bowman capsule of individual renal corpuscles is thickened in some places. The mesangial matrix is ​​expanded in some places, the number of mesangial and sometimes endothelial cells in individual renal corpuscles is slightly increased. Conclusion. Two weeks of nalbuphine use leads to changes in the renal corpuscle, which are still evident four weeks after drug withdrawal.